Reaction of non-cucurbitacea to Monosporascus spp. - Bento Tavares, Moises (2022)
With the recent discovery of five new species of the Monosporascus genus, a fungal genus involved in “Monosporascus root rot and vine decline,” pathogenicity studies have become important to understand the impact of these new species on cultivated plants, mainly on plant species used as an alternative for crop rotation. This study aimed to evaluate the pathogenicity of Monosporascus spp. in non-cucurbitaceous cultures. The tests were carried out in duplicate in a greenhouse in a completely randomized design, with the treatments: One isolate of each species of Monosporascus (M. brasiliensis, M. caatinguensis, M. cannonballus, M. mossoroensis, M. nordestinus, and M. semiaridus) and the absolute control, and five cultures (cowpea, jack bean, corn, sorghum, and bell pepper). Seeds of these cultures were sown in pots containing soil + Tropstrate HT® (ratio 2:1, v / v), previously inoculated with wheat seeds colonized with the species of Monosporascus. After 50 days of sowing, plants were evaluated for incidence, disease severity, length of shoot and roots, fresh and dry weight of shoots and roots. All inoculated Monosporascus species were able to induce damage in cowpea and bell pepper cultures, with M. cannonballus being the most aggressive. Corn, jack beans, and sorghum presented few or no symptoms of the disease and may be indicated as alternative cultures to be used in crop rotation with cucurbits. Studies with a greater number of isolates and cultivars for each culture tested in this study should be carried out to strengthen the data obtained.